THE PERCEPTION OF KADUNA AND KATSINA STATES SPORTS COUNCIL ATHLETES ON THE INCLUSION OF TRANSGENDER ATHLETES IN SPORTS (FUDMA JOURNAL OF SCIENCES, 2025)
This study examined the perception of Kaduna and Katsina State Sports Councils Athletes on the inclusion of transgender athletes in sports. The target population was all the Six hundred and twelve (612) registered athletes in both Kaduna and Katsina States. A total of two hundred and thirty-four (234) samples were selected for the study using simple random sampling technique. The instrument used for this study was a researchers’ designed questionnaire. (RDQ) After the face and content validity of the instrument by three (3), two (2) experts in the Department of Human Kinetics and Health Education and one (1) in the Department of Psychology and Guidance and counselling all in the Faculty of Education, Federal University Dutsin-Ma, the instrument was pilot-tested using Twenty (20) respondents from the Kaduna State Sports Council who do not take part in the main field work. The collected facts from the pilot-testing was analyze using Cronbach Alpha and the value of 0.8 was the results of the findings. After the administration of the research instrument, the data collected were analyzed using descriptive statistic of mean, standard deviation and t-test inferential statistics. The decision is taken at 2.50. Mean above 2.50 is accepted while mean below 2.50 is rejected. The findings of the study revealed that transgender individuals referred to people who belong to the third gender, person assigned female at birth that lives full time as male, those who wish to be socially recognized as a gender distinct from assigned sex with...
Keywords: Transgender; Transwomen; Transmen; Athletes; Cisgender; Sports Council